Annual Premium Determination for Joint Life Insurance with De Moivre and Gompertz’s Mortality Laws - Seftina Diyah Miasary (Square : Journal of Mathematics and Mathematics Education, 2022)
This research discusses how to determine the annual premium for joint life status. The death rate (mortality rate) is one of the factors that can be considered when calculating the premium. The quantitative method used in this study was to estimate the parameters of the De Moivre and Gompertz’s Mortality laws using secondary data from the 2011 Indonesian Mortality Table (TMI III) for men and women. This calculation generates a formula for calculating the annual premium for joint life insurance based on De Moivre and Gompertz mortality law. Starting with estimating the parameters of Gompertz's mortality law for the Indonesian Mortality Table in 2011 using the maximum likelihood estimation method, then calculating the combined life probability, death benefit APV, continuous life annuity APV, and annual premium for joint life insurance. The value of the annual premium on joint life insurance with the mortality law of De Moivre and Gompertz for a simulated term life insurance n = 10 years with age x (husband) 28 years and y (wife) 25 years, the death benefit (R) is Rp. 50,000,000; and the interest rate is 3.50 percent with the Indonesian Mortality Table in 2011. According to the calculations, the annual premium value of joint life insurance based on Gompertz's mortality law is greater than De Moivre's mortality law.Keywords: Join Life Insurance, Mortality Laws, Annual Premium.